The Effect of China's Two-Child Policy on the Child Sex Ratio: Evidence From Shanghai, China - Di Tang PhD; Xiangdong Gao PhD; Jiaoli Cai PhD; Peter. C. Coyte PhD (SAGE Publishing, 2022)
Objective: The bias towards males at birth has resulted in a major imbalance in the Chinese sex ratio that is often attributed to China's one-child policy. Relaxation of the one-child policy has the potential to reduce the imbalance in the sex ratio away from males. In this study, we assessed whether the bias towards males in the child sex ratio was reduced as a result of the two-child policy in China. Medical records data from one large municipal-level obstetrics hospital in Shanghai, East China. Design: Matching and difference-in-differences (MDID) techniques were used to investigate the effect of the two-child policy on the imbalance in the sex ratio at birth after matching for pregnancy status and socioeconomic factors. Results: Analyzing 133,358 live births suggest that the relaxation of the one-child policy had a small, but statistically significant effect in reducing the imbalance in the male to female sex ratio at birth. Conclusion: The results demonstrate that relaxation of the one-child policy reduced the imbalance in the male to female sex ratio at birth from 1.10 to 1.05 over the study period at one of the major obstetrics and gynecology hospitals in China.